{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

Advanced Engineering Mathematics Dennis G Zill 2nd Solution

# Advanced Engineering Mathematics Dennis G Zill 2nd Solution...

This preview shows pages 1–3. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: -4-2 2 4 t-4-2 2 4 X 1 Introduction to Differential Equations Exercises 1.1 1. Second-order; linear. 2. Third-order; nonlinear because of ( dy/dx ) 4 . 3. The differential equation is first-order. Writing it in the form x ( dy/dx ) + y 2 = 1, we see that it is nonlinear in y because of y 2 . However, writing it in the form ( y 2 − 1)( dx/dy ) + x = 0, we see that it is linear in x . 4. The differential equation is first-order. Writing it in the form u ( dv/du )+(1+ u ) v = ue u we see that it is linear in v . However, writing it in the form ( v + uv − ue u )( du/dv ) + u = 0, we see that it is nonlinear in u . 5. Fourth-order; linear 6. Second-order; nonlinear because of cos( r + u ) 7. Second-order; nonlinear because of p 1 + ( dy/dx ) 2 8. Second-order; nonlinear because of 1 /R 2 9. Third-order; linear 10. Second-order; nonlinear because of ˙ x 2 11. From y = e − x/ 2 we obtain y = − 1 2 e − x/ 2 . Then 2 y + y = − e − x/ 2 + e − x/ 2 = 0. 12. From y = 6 5 − 6 5 e − 20 t we obtain dy/dt = 24 e − 20 t , so that dy dt + 20 y = 24 e − 20 t + 20 µ 6 5 − 6 5 e − 20 t ¶ = 24 . 13. From y = e 3 x cos2 x we obtain y = 3 e 3 x cos2 x − 2 e 3 x sin2 x and y = 5 e 3 x cos2 x − 12 e 3 x sin2 x , so that y − 6 y + 13 y = 0. 14. From y = − cos x ln(sec x + tan x ) we obtain y = − 1 + sin x ln(sec x + tan x ) and y = tan x + cos x ln(sec x + tan x ). Then y + y = tan x . 15. Writing ln(2 X − 1) − ln( X − 1) = t and differentiating implicitly we obtain 2 2 X − 1 dX dt − 1 X − 1 dX dt = 1 µ 2 2 X − 1 − 1 X − 1 ¶ dX dt = 1 2 X − 2 − 2 X + 1 (2 X − 1)( X − 1) dX dt = 1 dX dt = − (2 X − 1)( X − 1) = ( X − 1)(1 − 2 X ) . Exponentiating both sides of the implicit solution we obtain 2 X − 1 X − 1 = e t = ⇒ 2 X − 1 = Xe t − e t = ⇒ ( e t − 1) = ( e t − 2) X = ⇒ X = e t − 1 e t − 2 . Solving e t − 2 = 0 we get t = ln2. Thus, the solution is defined on ( −∞ , ln2) or on (ln2 , ∞ ). The graph of the solution defined on ( −∞ , ln2) is dashed, and the graph of the solution defined on (ln2 , ∞ ) is solid. 1-4-2 2 4 x-4-2 2 4 y Exercises 1.1 16. Implicitly differentiating the solution we obtain − 2 x 2 dy dx − 4 xy + 2 y dy dx = 0 = ⇒ − x 2 dy − 2 xy dx + y dy = 0 = ⇒ 2 xy dx + ( x 2 − y ) dy = 0 . Using the quadratic formula to solve y 2 − 2 x 2 y − 1 = 0 for y , we get y = ( 2 x 2 ± √ 4 x 4 + 4 ) / 2 = x 2 ± √ x 4 + 1. Thus, two explicit solutions are y 1 = x 2 + √ x 4 + 1 and y 2 = x 2 − √ x 4 + 1. Both solutions are defined on ( −∞ , ∞ ). The graph of y 1 ( x ) is solid and the graph of y 2 is dashed. 17. Differentiating P = c 1 e t / (1 + c 1 e t ) we obtain dP dt = (1 + c 1 e t ) c 1 e t − c 1 e t · c 1 e t (1 + c 1 e t ) 2 = c 1 e t 1 + c 1 e t [(1 + c 1 e t ) − c 1 e t ] 1 + c 1 e t = P (1 − P ) ....
View Full Document

{[ snackBarMessage ]}